MEASUREMENT OF FORCED VITAL CAPACITY (FVC) IN ACUTE NEUROMUSCULAR WEAKNESS. Issue 12 (15th November 2016) - Randall, Anna; Aji, Baba
Abstract : Background: Prompt assessment for respiratory muscle weakness in patients with acute neuromuscular weakness is recommended by national guidelines. Failure to recognize this leads to increased morbidity and mortality. We set out to quantify the problem and suggest ways for improving care. Aim: To examine adherence to national guidelines for the identification of respiratory muscle weakness in patients with acute neuromuscular disease. Method: Retrospective analysis of anonymised electronic case notes for patients admitted to a district general hospital within the period 1st January 2015 to 1st January 2016. Patients were identified by coding criteria; diagnosis Guillain-Barré syndrome, Myasthenia gravis, Lambert-Eaton syndrome, or having received intravenous immunoglobulin. Results: Forced vital capacity (FVC) was requested at diagnosis in 38%. FVC was performed after the request in 45%. FVC was requested at any point during admission in 82%. The longest duration between request and completion of FVC was 5 days. Conclusions: There are significant delays in recognizing the need for FVC measurement, and in some cases is missed entirely. When identified, measurement does not take place in more than half the population, and there are serious delays. The potential for harm is great, and in two cases led to ITU admission.